Applied Economics / An Introductory Course - Griffins Alan; Wall Stuart (Longman, 1995)
This book provides a highly readable, yet suitably rigorous introduction to applied economics. Preface, Acknowledgements, Changes in the UK Economic Structure, Company Accounts as a Source of Financial Information, Firm Objectives and Firm Behaviour, The Small Firm, Mergers and Acquisitions in the Growth of the Firm, Oligopoly, The Multinational Corporation, Privatization and the Nationalized Industries, Pricing in Practice, Economics of the Environment, Transport, Social Policy, Consumption and Saving, Investment, Public Expenditure, Taxation, The UK Financial System, Money, Inflation, Unemployment, Regional and Urban Policy, Trade Unions and Wages and Collective Bargaining, Distribution of Income and Wealth, Exchange Rates, United Kingdom Trade Performance, Free Trade and Regional Trading Blocs and Protectionism, Managing the Economy, The European Union, International Money, A Guide to Sources.